Analysis of the Settling Ponds Effectiveness in Reducing the Quality of Bauxite Ore Mining Wastewater: Analisis Efektivitas Settling Pond dalam Menurunkan Mutu Air Limbah Tambang Bijih Bauksit - Rudy Mohammad Sairuddin; Tuhu Agung Rachmanto; Akmal Dzikri Maulana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This study aims to evaluate the effectiveness of the Settling Pond (SP) system in reducing the pollutant load of bauxite ore mining wastewater and formulate technical recommendations for optimizing its performance. The evaluation was conducted through analysis of water quality parameters (Total Suspended Solid/TSS, pH, Fe, and Mn) and hydraulic characteristics using Reynolds (Re) and Froude (Fr) numbers. The SP system studied consisted of 10 units with four compartments involving gravity sedimentation processes and the addition of coagulant chemicals. The results of the study showed that the TSS removal efficiency reached 94%, with a decrease in concentration from 1,200 mg/L at the inlet to 120 mg/L at the outlet. Hydraulic conditions showed laminar flow (Re < 500) and subcritical (Fr < 1) which supported the optimal sedimentation process. The effluent quality met environmental quality standards according to applicable regulations. This study confirms that the SP system plays an important role as a water pollution control technology in bauxite mining activities. Optimization of residence time, coagulant dosage adjustment, and routine maintenance are recommended to continuously improve system performance.